Comparison between Traditional Classroom and Flipped Classroom on Student’s Engagement and Satisfaction - Sarker, Pramath Chandra; Siddique, Md. Nur-E-Alam; Sultana, Sabina; Pal, Subrata Kumer (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Background: The implications of flipped classrooms are increasing day by day around the world for better benefits compared to traditional classrooms. But the application and research about this field are insufficient in Bangladesh Objective: The present study was conducted to investigate the effectiveness of the flipped classroom learning environment on students’ engagement and satisfaction compared to a traditional classroom. Methods: Result showed a significant difference in student engagement and satisfaction with flipped classroom being favored over traditional classroom. A cross-sectional survey research was conducted using a 5-point Likert-type questionnaire to measure student engagement and satisfaction, respectively, on both the traditional classroom and the flipped classroom. Data were collected from 79 participants from the traditional classroom and 61 participants from the flipped classroom. After six weeks of intervention on flipped classroom method, again a survey was carried out to discover student engagement and satisfaction. The obtained data were analyzed by employing descriptive statistics, t-test, and correlation by SPSS version 26, Microsoft Excel version 19, and an online t-test calculator. Results: The study's findings revealed a significant mean difference in student engagement and satisfaction between the traditional and flipped classrooms. The outcomes also showed that students were more engaged and satisfied with flipped classrooms than with traditional classrooms. Another outcome to note is that the flipped classroom was also able to differentiate students based on class activity and regularity, while the traditional classroom could not. Conclusion: The findings suggest that the flipped classroom model has the potential to be the ideal education system in the 21st century and to address the 4th Industrial Revolution. Further investigation, assessment, and modification are necessary for widespread implementation.